Assertiveness Training Melalui Bermain Peran dalam Bimbingan Kelompok untuk Meningkatkan Komunikasi Interpersonal - Sembiring, Kristinus (Psikopedagogia, 2016)
This study aimed to find out the improvement of students’ interpersonal communication skill after coming to assertiveness training through role play method in group guidance. This was a quasi-experimental study with nonequivalent control group design. The number of subjects in this study was ten people in the experimental group and ten people in the control group. The subject of this study was taken by using purposive sampling technique. The data collection instrument for this study was valid and reliable interpersonal communication scale. The data analysis technique in this study was the nonparametric statistic with Mann Whitney U Test or Wilcoxon Rank Sum Test. The result of the data analysis showed that there was a significant difference between the score of experimental and group control. It means that assertive training through role play in group guidance was more effective to improve students’ interpersonal communication skill than the implementation of group guidance without assertiveness training. The result of this study showed that the use of assertiveness training through role play was an effective method in group guidance service for improving students' interpersonal communication. The school counselor can utilize the result of this study to improve the students’ interpersonal communication by using assertiveness training strategy through role play in group guidance service.